Using implicit encouragement to increase narrative productivity in children: Preliminary evidence and legal implications. Issue 4 (2nd October 2018) - Olaguez, Alma P.; Castro, Amy; Cleveland, Kyndra C.; Klemfuss, J. Zoe; Quas, Jodi A.
Abstract: Statements made by children in a range of legal settings can irrevocably impact their family structure, relationships, and living environment. Because these statements can fundamentally alter children's futures, efforts have been made to identify methods to enhance children's reports by increasing comprehensiveness, completeness, and accuracy. Interviewer support has broadly been considered a method of interest, but variations in what constitutes "support" have highlighted the need for greater specificity in documenting how different facets of supportive behaviors relate to children's reporting tendencies. In this review, we describe work focused on the effects of interviewer support, on children's memory completeness and accuracy. We then describe to a subset of interviewer behaviors that encourage elaboration in dyadic interactions: back-channeling and vocatives. We present preliminary evidence suggesting that these utterances, referred to as implicit encouragement, can increase the amount of detail provided without compromising accuracy. Implications for custody evaluations are discussed.